2014
DOI: 10.1242/dev.098871
|View full text |Cite
|
Sign up to set email alerts
|

Induction of endocycles represses apoptosis independently of differentiation and predisposes cells to genome instability

Abstract: The endocycle is a common developmental cell cycle variation wherein cells become polyploid through repeated genome duplication without mitosis. We previously showed that Drosophila endocycling cells repress the apoptotic cell death response to genotoxic stress. Here, we investigate whether it is differentiation or endocycle remodeling that promotes apoptotic repression. We find that when nurse and follicle cells switch into endocycles during oogenesis they repress the apoptotic response to DNA damage caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 116 publications
11
102
0
Order By: Relevance
“…We previously proposed that the apoptotic response to genotoxic stress must be tightly repressed in polyploid endocycling cells because they have constitutive genotoxic stress caused by under-replication of heterochromatic DNA [19], [83], [84]. Consistent with a possible linkage between the endocycle program and apoptotic repression, we recently found that experimentally-induced endocycling cells (iECs) repress apoptosis independent of cell differentiation [25]. It is clear that low levels of p53 protein is not the only mechanism of repression because over-expression of p53A resulted in abundant protein in endocycling cells, but failed to induce H99 transcription or apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…We previously proposed that the apoptotic response to genotoxic stress must be tightly repressed in polyploid endocycling cells because they have constitutive genotoxic stress caused by under-replication of heterochromatic DNA [19], [83], [84]. Consistent with a possible linkage between the endocycle program and apoptotic repression, we recently found that experimentally-induced endocycling cells (iECs) repress apoptosis independent of cell differentiation [25]. It is clear that low levels of p53 protein is not the only mechanism of repression because over-expression of p53A resulted in abundant protein in endocycling cells, but failed to induce H99 transcription or apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…Western blotting was performed as previously described. 74,75 Antibody dilutions are: mouse anti p53 (C11, Santa Cruz, Dallas, TX, USA) 1 : 500, mouse anti-α-tubulin (clone DM1A, Sigma-Aldrich Corp., St. Louis, MO, USA) 1 : 5000, and anti-mouse secondary antibody, peroxidase labeled (KPL, Gaithersburg, MD, USA) at 1 : 5000.…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to ionizing radiation, polyploid cells accumulate double-stranded DNA breaks, yet repress the DNA damage response checkpoint. 47 In addition, genetically inducing an endocycle is sufficient to make a cell more resistant to apoptosis 47 thereby giving polyploid cells a survival advantage. Polyploidy has also long been correlated with an increased resistance to stress.…”
Section: The Polyploid Advantagementioning
confidence: 99%